Sexual Punishments - Ristroph, Alice (Columbia Journal of Gender and Law, 2006)
The claim that incarceration is a sexual punishment-the central claim of this Article-may be disputed with respect to both the adjective and the noun. The challenge to the choice of noun is this: any sex, including sexual assaults, that may occur in prison is “not part of the penalty.”‘ Only officially sanctioned deprivations of rights and liberties are properly called “punishment,” and since no prisons officially sanction inmate sex and most officially condemn it, sex in prison is not penal. In other words, the prison rapist is not an arm of the state. The challenge to the adjective is this: “sex” in prison is not really “sexual.” The word “sexual” should be reserved to describe a realm of erotic desire and physical gratification, and there is much evidence that the physical interactions and threatened assaults that occur in prison, even the ones that involve genitals, are expressions of dominance and power that have little to do with desire. In short, coerced intercourse in prison is violent, inhumane, and illegal-it is not sexual, and it is not punishment.